Effects of a major earthquake on blood donor types and infectious diseases marker rates - (:unkn) unknown (WILEY, 2005)
This observational study attempted to identify the effect of a natural disaster on the safety of blood supply and donor types with the influx of donors after a severe earthquake. Blood donation rate, blood discard rate and safety of blood donations responding to the earthquake, as projected from the infectious disease marker rate, were evaluated in blood donated immediately before (1 July-17 August) and after 17 August 1999 (17 August-21 August). These were compared with the results from the corresponding periods in 1998 and 2000 for donations at a university medical centre and two regional blood centres. 8055 units of allogeneic blood were collected at two regional blood centres, and 450 units were collected at a university medical centre during 4 days. Viral marker rates were nearly the same at the former but were slightly lower at the latter. The blood discard rate was nearly twice the comparative periods at the former, but it remained unchanged at the latter. Voluntary donors replaced the replacement donors during 4 days. This analysis highlights the size of the pool of potential donors that are available as a national resource that can be motivated to give blood with the right motivation.
Keywords: blood donation; blood safety; donor types; earthquake; viral markers; SEPTEMBER-11; DISASTER; SAFETY